PERLINDUNGAN HUKUM PERDATA DALAM HAL PEMBAJAKAN ATLET E-SPORT ANTARAATLET DENGAN PT. ECHO E-SPORTS INDONESIA - Melani Harly; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2022)
Agreement is an event when someone has promised or when one person with another person makes an agreement with each other between the two parties.In this study the author will discuss the existing agreements in E-Sports. The definition of E-Sports itself is an electronic game that is competitive in nature. In this case, the author is interested in analyzing legal problems that may occur in E-Sports athletes, such as doing actions that can harm other parties and not fulfilling the agreements that have been signed in the E-Sports contract. One of the problems that the author will discuss is regarding the piracy of E-Sports athletes or can be called Poaching. Poachingcomes from English which means piracy or illegal hunting. Things like this can also be referred to as contract breaches or breaches of contract. The purpose of this study is to provide readers with an understanding of the forms of protection against unwanted actions that occur in the world of E-Sports. The method used to answer the problems that have been formulated in this study is a normative legal research method.